Serum pepsinogen and gastrin-17 as potential biomarkers for pre-malignant lesions in the gastric corpus - Loong, TH; Soon, NC; Mahmud, NRKN; Naidu, J; Rani, RA; Elias, MH; Rose, IM; Tamil, A; Mokhtar, NM; Ali, RAR; Nazefah Abdul Hamid (Spandidos Publ Ltd, 2024)
Indexed by SCOPUS